Along the Folds: Sea and Spar and Portals Between. Issue 2 (August 2016) - Moulthrop, Stuart; Schumaker, Justin
Abstract : This article employs the concept of the fold, in part as developed by Deleuze out of Leibniz, as an approach to its own attempt at folding together the discourses of literature and game study. On the game side we consider Portal 2 (2011), and from the literary area, the generative mega-poem 'Sea and Spar Between' (2010). Though formally disparate, both texts employ a unit operation of folding, applying to virtual space in the game and to verbal space in the systemic poem. We inquire into how the structure of implication in both cases leads to an irruption of the technological sublime, an encounter with spaces and magnitudes that escape both human and computational reckoning. Drawing on Myers's concept of 'anti-ness' as a feature of play, we conclude that further discussion of games and literature, the main concern of cybertextual studies, requires more complex structure than symmetry or zero-sum relations.